Utility of WAIS-IV Digit Span indices as measures of performance validity in moderate to severe traumatic brain injury. Issue 7 (3rd October 2022) - Kanser, Robert J.; Rapport, Lisa J.; Hanks, Robin A.; Patrick, Sarah D.
Abstract: Objective: The addition of Sequencing to WAIS-IV Digit Span (DS) brought about new Reliable Digit Span (RDS) indices and an Age-Corrected Scaled Score that includes Sequencing trials. Reports have indicated that these new performance validity tests (PVTs) are superior to the traditional RDS; however, comparisons in the context of known neurocognitive impairment are sparse. This study compared DS-derived PVT classification accuracies in a design that included adults with verified TBI. Methods: Participants included 64 adults with moderate-to-severe TBI (TBI), 51 healthy adults coached to simulate TBI (SIM), and 78 healthy comparisons (HC). Participants completed the WAIS-IV DS subtest in the context of a larger test battery. Results: Kruskal–Wallis tests indicated that all DS indices differed significantly across groups. Post hoc contrasts revealed that only RDS Forward and the traditional RDS differed significantly between SIM and TBI. ROC analyses indicated that RDS variables were comparable predictors of SIM vs. HC; however, the traditional RDS showed the highest sensitivity when approximating 90% specificity for SIM vs. TBI. A greater percentage of TBI scored RDS Sequencing < 1 compared to SIM and HC. Conclusion: In the context of moderate-to-severe TBI, the DS-derived PVTs showed comparable discriminability. However, the Greiffenstein et al. traditional RDS demonstrated the best classification accuracy with respect to specificity/sensitivity balance. This relative superiority may reflect that individuals with verified TBI are more likely to perseverate on prior instructions during DS Sequencing. Findings highlight the importance of including individuals with verified TBI when evaluating and developing PVTs.